Pengaruh Perlakuan Panas Quenching dan Tempering terhadap Laju Korosi pada Baja AISI 420 - Sotya Anggoro (Proklamasi 45 University, 2017)
Corrosion occurs in almost all metals. Even corrosion-resistant metals are corroded, but their corrosion rate is different from ordinary or non-corrosion resistant metals. This study examines the corrosion rate that occurs in stainless steel that is stainless steel. Stainless steel contains high enough chromium levels that can reduce the rate of corrosion that occurs. The metal material to be studied is the AISI 420 steel, which belongs to the Martensitic Stainless Steel class. This study examined the effect of heat treatment on corrosion rate and hardness level of AISI 420 steel. The heat treatment carried out was Quenching at 1020oC with a holding time of 60minutes with an oil cooling medium. After quenching the subsequent heat treatment is tempering with temperature variations of temperature 200oC and 300oC with a resistance time of 45 minutes and air cooling media. The results of this study showed that the base material specimens had the highest corrosion rate of 0.569 mm/y. The lowest corrosion rate is in specimens with quenching process with a value of 0.267 mm/y. The highest Vickers hardness values were found in specimens with quenching process with a value of 551 kg/mm2. The lowest hardness value is in the specimen with tempering process at 300oC with 405 kg/mm2.